Peningkatan Kemampuan Berpikir Kritis dan Hasil Belajar Biologi Siswa Kelas VII-A Melalui Penerapan Model Guided Inquiry dengan Bantuan Social Network Facebook di SMPN 1 Kartasura - Fildza Hilfi Fanani; Riezky Maya Probosari; Suciati Sudarisman (Universitas Sebelas Maret, 2014)
This study is aimed at improving the students’ critical thinking ability and achievement in Biology of VII A class of SMPN 1 Kartasura through the implementation of guided inquiry model assisted by the use of facebook. This research is a classroom action research involving several cycles in which each cycle includes four stages those are planning, action, observation, and reflection. The subject of this research is the students of VII A class at SMPN 1 Kartasura in academic year of 2012/2013. The data are obtained through the test (essay and multiple-choice) and non-test (observation, interviews and questionnaires). The data are analyzed through descriptive analytical techniques and validated through triangulation techniques. Critical thinking ability consists of six aspects those are interpretation, analysis, evaluation, inference, explanation, and self-regulation. The average improvement percentage of critical thinking ability test in Pre-cycle, Cycle I, Cycle II, and Cycle III sequently are (41,36%; 52,66%; 65,32%; 77,26%). Students’ achievement is viewed from the increase of student learning completeness consisting of cognitive, psychomotor, and affective. The result of percentage attainment average from cognitive aspects in Pre-cycle, Cycle I, Cycle II, and Cycle III sequently are (36,11%; 47,22%; 72,22%; 100%). Psychomotor students’ achievement consists of three aspects, those are stringing experimental tool, observing the object changes that occur in the experiment, and communicating the results of experiments and worksheets in the presentation. The result of percentage attainment average from psychomotor aspects in Cycle I, Cycle II, and Cycle III sequently are (64,12%; 81,25%; 90,66%). Affective students’ achievement includes three aspect which are being meticulous in observing object from results of the experiment, being discipline in collecting worksheets, and being cooperative in a group discussion. The result of percentage attainment average from affective aspects in Cycle I, Cycle II, and Cycle III sequently are (61,81%; 77,31%; 91,92%). Based on the results of the research it can be concluded that the implementation of guided inquiry model assisted by the use of facebook can improve the students’ critical thinking ability and achievement in Biology of VII A class of SMPN 1 Kartasura. Key Words: Guided Inquiry, Facebook, Biology Critical Thinking Ability, Students’ Achievement in Biology